Closing Water‐Related Loops in High‐tech Polymer Production – Status, Perspectives and Limitations. Issue 10 (21st June 2019) - Blöcher, Christoph; Schießer, Yuliya; Weber, Rainer
Abstract: Chemical production is inherently associated with the use of a significant amount of water. The closure of water‐related loops to recover materials and reuse water has been established in chemical parks for a long time. Circuits can be realized process‐integrated, across legal entities, or even cross‐sectoral. Incentives can be the lack of natural water resources, to use a high water quality or the recovery of valuables. One example is the recovery of NaCl from salt‐containing process water streams to produce chlorine and caustic soda in the chlor‐alkali electrolysis. However, such reuse schemes exhibit technical, economic and ecological challenges. Taking these into account, industry is taking action to research and develop new, environmentally friendly and economically viable processes. Abstract : The closure of water‐related loops in the chemical industry is essential to further take forward environmentally viable production processes. An example is the recovery of NaCl from salt‐containing process water streams. Such reuse schemes exhibit technical, economic and ecological challenges. The paper addresses what is achieved already, and which developments are on their way.